Design and optimisation of radio-frequency probes for high field magnetic imaging - Alsuraihi, Amany Ali (2011)
This thesis addresses the inhomogeneity and the high SAR values associated with the state-of-art 7 T high field MR system. The high signal to noise ratio associated with such high field systems ≥ 7 T is a continuous driver to use such systems where high resolution images are acquired at short acquisition time. However, these systems come with many challenges. The central brightening effect in MR images indicates a B1 degraded field uniformity. For example, at 7 T with an operational electromagnetic frequency of 298 MHz the wavelength is about 12 cm in tissues. At such short wavelengths, circuit and electromagnetic theory will be invalid an analytical solution and is no longer feasible to predict magnetic field distribution. In this thesis the full wave method, Transmission Line Modelling (TLM) technique is used in conjunction with Tikhonov regularisation inverse method in order to optimise phases and amplitude of elementary drive currents of four different coils for optimal uniformity and low SAR values. Two dimensional 8 and 16 rungs birdcage-like coils were first optimised. Then the optimisation was carried out for the three dimensional problem for 8 and 16 rungs birdcage-like coils and then compared to 32 and 64 multi-element coils. The travelling wave approach is a recent approach to overcome field inhomogeneity and high SAR values. An Antenna is used to couple head/body to a travelling wave RF signal. Using Finite Difference Time Domain (FDTD) method, a patch antenna has been designed, and the effect of using matching load for maximising the power flow in the magnet bore, field uniformity and reducing SAR values in the head have been explored. An end tapered waveguide has been designed for local imaging and tested on the 7 T Philips Acheiva system. Further developments have been suggested for the end tapered waveguide by suggesting the design of a dielectric transformer. It is envisaged that the waveguide approach is ideally suited for a multi-transmit system which would employ a number of waveguide ports.